2015
DOI: 10.1590/s0100-736x2015000700006
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to β-lactam and tetracycline in Campylobacter spp.isolated from broiler slaughterhouses in southern Brazil

Abstract: RESUMO.-[Resistência a β-lactâmicos e tetraciclina emCampylobacter spp. isolados de matadouros-frigorífi-cos de aves no sul do Brasil.] O presente estudo foi realizado para examinar e analisar as características genéticas de resistência antimicrobiana de Campylobacter spp. a partir de fontes avícolas. Um total de 141 amostras de Campylobacter isolados em matadouros-frigoríficos de aves do estado do Rio Grande do Sul, Brasil, foi identificado por mé-todos fenotípicos e genotípicos. Foi analisada a susceptibilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“…Emerging resistance to the antimicrobial agents of choice for treating Campylobacter infections is becoming a serious threat to public health (Du et al, 2018). The frequency of MDR strains found in this study is similar to that in previous reports from Brazil (Sierra-Arguello et al, 2015). Given such results, Brazilian authorities should consider establishing an integrated surveillance network for antibiotic resistance in Campylobacter.…”
Section: Antimicrobial Resistance In Campylobacter Jejunisupporting
confidence: 85%
See 2 more Smart Citations
“…Emerging resistance to the antimicrobial agents of choice for treating Campylobacter infections is becoming a serious threat to public health (Du et al, 2018). The frequency of MDR strains found in this study is similar to that in previous reports from Brazil (Sierra-Arguello et al, 2015). Given such results, Brazilian authorities should consider establishing an integrated surveillance network for antibiotic resistance in Campylobacter.…”
Section: Antimicrobial Resistance In Campylobacter Jejunisupporting
confidence: 85%
“…A total of 28 isolates had tetracycline MICs ≥2 mg/L, and 42.8% of them carried the gene. Reports from Brazil have shown lower frequencies of this gene than in other countries (Sierra-Arguello et al, 2015;Du et al, 2018). This gene can be present in conjugative plasmids containing resistance genes for other antimicrobials that continue to undergo selective pressure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ampicillin, like tetracycline, shows activity against Campylobacter, but in general, both are not recommended for the treatment of campylobacteriosis because the rates of resistance of these antimicrobials are too high to be useful [62]. The results obtained by these authors showed that 65% of Campylobacter isolates from broiler slaughterhouses in southern Brazil were resistant to β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…É um mecanismo adquirido por mutação genética relacionada com o gene cmeB que altera a expressão das proteínas reguladoras das bombas de efluxo natural da bactéria, processo que induz o transporte ativo do antibiótico de dentro para fora da membrana, impedindo sua ação. Apesar de ser um mecanismo comum celular, com função de excreção de substratos naturais do metabolismo, a bactéria passa a utilizar este mecanismo através da codificação do gene cmeB que, com o gasto energético, faz com que as bombas expulsem o fármaco que ultrapassou a parede celular (ALCALDE-RICO et al, 2016;SIERRA-ARGUELLO et al, 2015).…”
Section: Características Genotípicas Dos Mecanismos De Resistênciaunclassified